Case Report: Persistent response to combination therapy of pemigatinib, chemotherapy, and immune checkpoint inhibitor in a patient with advanced intrahepatic cholangiocarcinoma - Zhang, Zhuochao; Wang, Gaofei; Du, Lei; Zhao, Jie; Pan, Lichao; Zhang, Gong; Wang, Fei; Liu, Rong (Frontiers in Immunology, 2023)
Patients with advanced intrahepatic cholangiocarcinoma (iCCA) often have a poor prognosis. Recent advancements in targeted molecular therapy and immunotherapy have been made. Herein, we report a case of advanced iCCA treated with a combination of pemigatinib (a selective FGFR inhibitor), chemotherapy, and an immune checkpoint inhibitor. A 34-year-old female was diagnosed with advanced iCCA with multiple liver masses and metastases in the peritoneum and lymph nodes. Next-generation sequencing (NGS) identified the genetic mutations. An FGFR2-BICC1 gene fusion was found in this patient. The patient was treated with pemigatinib in combination with pembrolizumab plus systemic gemcitabine and oxaliplatin. After 9 cycles of the combination therapy, the patient achieved a partial response, complete metabolic response, and normalization of tumor markers. Sequentially, the patient received pemigatinib and pembrolizumab for 3 months. Due to the elevated tumor biomarker, she is currently receiving chemotherapy, pemigatinib, and pembrolizumab treatment again. She regained an excellent physical status after 16 months of treatment. To the best of our knowledge, this was the first reported case of advanced iCCA successfully treated with a combination of pemigatinib, chemotherapy, and ICIs as a first-line regimen. This treatment combination may be effective and safe in the advanced iCCA.